Heterogeneous Effects of Islamic Finance: A Multilevel Analysis for Policy Optimization in Developing Economies - Supriadi, Iman; Wany, Eva (Signifikan: Jurnal Ilmu Ekonomi, 2025)
Research Originality: This study addresses a gap in the literature by examining the heterogeneous impact of Islamic financial instruments. It incorporates various contextual factors and employs panel data regression to control for cross-country and temporal heterogeneity, offering a broader perspective on Islamic finance and economic growth.Research Objectives: This study analyzes the impact of Islamic financial instruments on economic growth in developing countries with different income levels over time.Research Methods: A quantitative approach is applied using panel data regression with pooled data classification to account for variations in data treatment.Empirical Results: The findings reveal that Islamic financial instruments, particularly Total Islamic Financing and Islamic Banking Assets, significantly enhance economic growth. Demographic factors, such as population size, also play a key role, while inflation has no significant impact. Additionally, Fixed Effects (Cross) values, which adjust for country- and year-specific heterogeneity, show substantial variation, with positive and negative values across countries and periods.Implications: These findings offer policy insights to help governments and regulators develop responsive, economic policies that promote financial inclusion, strengthen regulatory frameworks, and support sustainable growth through Islamic finance.JEL Classification: C33, F43, G21, O16How to Cite:Supriadi, I., & Wany, E. (2025). Heterogenous Effect of Islamic Finance: A Multilevel Analysis for Policy Optimization in Developing Economies. Signifikan: Jurnal Ilmu Ekonomi, 14(1), 197-216. https://doi.org/10.15408/sjie.v14i1.44736.